PENGARUH PENDEKATAN JELAJAH ALAM SEKITAR PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Anggreni, Desy; Tampubolon, Budiman; Sugiharto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the influenceof the approach of natural surroundings the learning outcomes of IIS 11th grade students of Taman Mulia High School in Kubu Raya Regency. The method used is the experimental method, the form of research used is "quasy experimental design". The source of this research data is all students of class XI SMA Taman Mulia kabupaten Kubu Raya and the data is the student's answer sheet for the final knowledge test. Data analysis techniques used formulas look for the mean (mean), t test. Based on the results of processing and analyzing data, the results of the study showed that the average student learning outcomes were not applied around 84.81 which was classified as good. but if the situation is different ie 1.67815 ≤ 3.7074 ≥ 1.67815 or t count ≥ t table ie 3.7074 ˃ 1.67815 then H0 is rejected at a significance level of 5% this means that Ha is accepted. So, there is a difference between the average learning outcomes of students who are taught using a natural surroundings approach with the average learning outcomes of students who use conventional learning Keywords: Influence,approach to exploring the natural surroundings, Learning Outcome